1999
DOI: 10.1073/pnas.96.17.9769
|View full text |Cite
|
Sign up to set email alerts
|

T cell ignorance in mice to Borna disease virus can be overcome by peripheral expression of the viral nucleoprotein

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
2
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 45 publications
5
61
2
2
Order By: Relevance
“…Thus, these results demonstrate that the kinetics of immune cell priming and virus spread are very important for the two possible outcomes of BDV infection in susceptible MRL mice, i.e., elimination or immunopathology. This notion is underscored by our previous finding that postexposure vaccination of symptomless persistently infected mice cannot clear the infection but rather induces immunopathology (27). Similar conclusions with respect to the delicate balance between protective and immunopathological effects of the antiviral T-cell response were drawn from BDV infection experiments using rats (38).…”
Section: Vol 79 2005 Ifn-␥ Mediates Borna Disease Virus Clearance Fsupporting
confidence: 62%
See 2 more Smart Citations
“…Thus, these results demonstrate that the kinetics of immune cell priming and virus spread are very important for the two possible outcomes of BDV infection in susceptible MRL mice, i.e., elimination or immunopathology. This notion is underscored by our previous finding that postexposure vaccination of symptomless persistently infected mice cannot clear the infection but rather induces immunopathology (27). Similar conclusions with respect to the delicate balance between protective and immunopathological effects of the antiviral T-cell response were drawn from BDV infection experiments using rats (38).…”
Section: Vol 79 2005 Ifn-␥ Mediates Borna Disease Virus Clearance Fsupporting
confidence: 62%
“…At this early time of infection, the levels of viral spread in the brains of old wild-type and GKO animals were comparable, indicating that BDV initially infected both types of mice but that the virus was later cleared from neurons of wildtype mice but not from those of GKO mice. We previously showed that brain-derived mononuclear cell preparations isolated from wild-type MRL mice infected as newborns contain around 30% CD8 T cells and around 10 to 15% CD4 T cells at the peak of neurological disease (27). We also showed previously that around 30% of the CD8 T cells were TELEISSI specific when labeled with a TELEISSI-H-2K k tetramer directly after isolation (14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural infection with BDV occurs in horses, sheep, and other species (21). Although natural BDV infection of mice has not been reported, BDV can replicate in the mouse CNS after intracerebral infection (10,11). However, most mouse strains are resistant to BDV-induced disease, and only mice of few strains, such as MRL, develop neurological disorder following infection with BDV (10,11).…”
mentioning
confidence: 99%
“…In rodents, BDV-specific CD8 + cytotoxic T lymphocytes (CTL) are mainly directed against the viral nucleoprotein N [17,18]. In mice of the H-2 k haplotype, the N-derived peptide TELEISSI represents the immunodominant CTL epitope [19].…”
Section: Introductionmentioning
confidence: 99%